A study on the effectiveness of sales promotion in stationery department of Jaya Jusco Bandar Baru Klang / W. Hasyusnita Wan Yusof - Wan Yusof, W. Hasyusnita (1996)
Responding to the important of promotion which can enhance the store sales and profitability, Jaya Jusco must find effective way of the stores promotion and centralized their marketing strategy towards the targeted customers. With the right sales promotion tools, the potential buyers will be aware of the store and products exists. As Jaya Jusco BBK is a new store opened at the Bukit Raja Shopping Centre and just celebrate its first Anniversary Sales in October 1996, the ability to achieve the targeted customers is hard. Eventhough there are many stores at other outlets such as at Wangsa Maju, Bandar Utaraa, Melaka which have been successful in built the loyalty of the customers to the stores, but there are many things Jaya Jusco can do in terms of creating customer's awareness and loyalty for their new customers. Chapter one will disscuss the background of the study and the Department overall. It includes problems facing in the purpose of the study, the objectives of the study, area and scope of the study and the limitations toward getting the data needecLThis study was done in such a way to get the performance and effectiveness of Jaya Jusco towards their sales promotion strategy as well as to the Stationery Department Chapter two it will disscuss the literature review of the sales promotion in the retail business, the important of the advertising and promotion tools in creating awareness of the customers towards the store and the product offers.